Why We Love Blue Hues on Websites: a fNIRS Investigation of Color and Its Impact on the Neural Processing of eCommerce Websites - Nissen, A. (NeuroIS Retreat, 2020)
Blue of all colors seems to be generally preferred by humans and animals. Consequently, the use of this color in ecommerce context has several positive effects such as increased trustworthiness and aesthetic ratings. These effects are, in this study, hypothesized to be caused by specific neural processes in the prefrontal cortex of human decision makers. Consequently, this study tackles the research question whether there is a distinct neural activation pattern for blue websites that helps to explain why blue is often most favored. To investigate this, one website is designed and manipulated in col-or to which user reactions are measured by employing functional near-infrared spectroscopy (fNIRS). The results of this study show that blue colored websites seem to require generally less processing power related to cognitive while revealing increases in brain structures related to processing pleasant and aesthetic stimuli.